Kajian Aktivitas Infeksi Rhizobium sp. Indigenus Pada Kerandang (Pueraria phaseoloides) - Triwahyuningsih, Nike; Pristiwantoro, Eko Cahyo; Utari, Lilik (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2005)
Kudzu, a kind  of  legume   cover  crops  (LCC),   plays  important   roles  in  soil and  water conservation. It is effective  for  inhibiting  erotion,  compaction  and leaching  of nutrients,  as well as to suppress weeds.  Plants growing with legume  ground covers usually show  better nutrition,   growth and yield. Recently,  this cover crops have been widely  used to prevent  the negative effects  and to improve  soil physical  and nutritional  characteristics. As a legume,  bacterial  inoculation   is to enhance  the infection and nodulation activity. A research  to observe  the role of indigenous  Rhizobium   on infection and nodulation  activity of kudzu was carried  out in September  till December 2004.  The research  was done in Regosol  volcanic  soil in Tlatar  Village  of Sawangan in Magelang district of Central  Java. A pot experiment   was arranged in 4x2 factorial    completely   randomized   design  which  was repeated   three times.   The  seedling   innoculation   with  root  nodules  endophytic   bacteria   was  to increase  nodulation  and to enhance  Kudzu  plant growth.   The seedlings  were inoculated  with  1, 2 and 3 ml/pot of grinded  root nodules  of wild plants  containing  endophytic  Rhizobium  sp.  The wild kudzu  plants were taken  from  coastal  sandy  land  of southern   Yogyakarta.   All treated seedlings were planted  in a sterilized  medium  to be compared  to the unsterilized  one in order to examine  the role of indigenous  bacterias. Observation  on bacterial infection activity, nodulation,  and plant growth were taken  at week  4, 6, 8, and  10. All the  datas  were  variance   analyzed   and the  treatments average  were  tested  with 5% level  of Duncan's multiple range test. The  results  showed  that  application   of 2 ml/pot  of innoculum significantly   increased  the infection  activity, nodulation  and plant growth. Sterilized  soil decreased  the infection  activity.   Since the innoculation  of endophytic Rhizobium  sp.  in unsterilized  soil significantly   increased the infection actifity,  nodulation  and plant growth,  so the indigenous  Rhizobium sp. in rhizhosfer  was needed to sinergisticaly  worked  well with inoculum  to increase  infection  activities   and root nodulation.